Uso del sistema vetiver (Chrysospogon zizanioides) para la remediación de suelos contaminados por metales pesados provenientes de la actividad minera - Leon Alarcon, Yoselin Santa (2019)
Mining activity contributes significantly to the contamination of water and soils, resources of great importance for the population's livelihood, which is why more care is required in case of any affectation is necessary its remediation, the current techniques of metal remediation heavy water and soil is highly expensive and often inefficient, has sought to immobilize, reduce and eliminate the toxicity of contaminants in soil and water using microorganisms and plants. Phytoremediation is a cleaning technology that makes use of the capacities that plants have to accumulate to metabolize, absorb and stabilize the different organic and inorganic compounds, which are found in soil and water body environments, many of them caused by mining activity, it is profitable and has aesthetic advantages and long applicability. The technology of vetiver grasses (Chrysopogon zizanioides) is an economical, simple and natural alternative to decontaminate components such as soil and groundwater and even the atmosphere with heavy metals.